2008
DOI: 10.1590/s1516-89132008000600003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity among Flue-cured Tobacco Cultivars Based on RAPD and AFLP Markers

Abstract: The aim of this work was to study the genetic diversity among flue-cured tobacco cultivars. RAPD and AFLP analyses were used to assess the genetic similarity among selected accessions of flue-cured tobacco. Seventy eight RAPD and 154 AFLP polymorphic bands were obtained and used to assess the genetic diversity among 28 tobacco accessions. The cultivar relationships were estimated through the cluster analysis (UPGMA) based on RAPD dataand AFLP data. The accessions were grouped into three major clusters and thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 7 publications
1
11
0
2
Order By: Relevance
“…In this study, molecular marker data based clustering of oriental tobacco genotypes did not pursuit agro-morphological based grouping. This is similar to finding of Yao Zhang et al (2008). Since, 77% of the total genomic DNA in cultivated tobacco is composed of repetitive sequences (NARAYAN, 1987), therefore, there is low amount of non-repetitive DNA in the genome of tobacco that responsible for any morphological and quality traits variation.…”
Section: Ssr Markerssupporting
confidence: 86%
See 2 more Smart Citations
“…In this study, molecular marker data based clustering of oriental tobacco genotypes did not pursuit agro-morphological based grouping. This is similar to finding of Yao Zhang et al (2008). Since, 77% of the total genomic DNA in cultivated tobacco is composed of repetitive sequences (NARAYAN, 1987), therefore, there is low amount of non-repetitive DNA in the genome of tobacco that responsible for any morphological and quality traits variation.…”
Section: Ssr Markerssupporting
confidence: 86%
“…In contrast to agro-morphological traits, there were not completely concurrences among geographical distribution of oriental-type genotypes and established clusters based on SSR marker data. Yao Zhang et al (2008) also indicated that dendrogram constructed by using RAPD and AFLP markers in flue-cured tobaccos could not indicate any clear pattern of their geographical origins.…”
Section: Ssr Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty decamer oligonucleotide primers (Sangon Bioengineering Technology Service Co. Ltd., Shanghai, China) ( Table 2) were used to amplify genomic DNA of 78-04, O. basilicum and five F 1 individuals following the previous protocol (Zhang HY et al, 2008) with small modifications. Amplification reactions were carried out in 25 µL solution containing 2.5 µL 10 × buffer; 2 µL, 2.5 mM dNTPs mixture; 1 µL, 10.0 mM primer; 1 µL genomic DNA; 0.5 µL (2 unit µL -1 ) Taq polymerase (Roche Diagnostics, Penzberg, Germany).…”
Section: Rapd Analysismentioning
confidence: 99%
“…Entretanto, tem sido observada considerável perda da variabilidade genética na cultura detectada mediante estudos em níveis morfológicos, isoenzimáticos e moleculares (Narayan, 1987;Khan & Narayan 2007;Zhang et al, 2008;Cruz et al, 2010), devido à preferência dos produtores por determinadas variedades e ao desenvolvimento de cultivares a partir de progenitores aparentados e seleção contínua para caracteres de interesse comercial (Zhang et al, 2008).…”
Section: Introductionunclassified